MANAGEMENT OF EDUCATIONAL FACILITIES AND INFRASTRUCTURE IN SCHOOLS - Yuniarti, Ira; Annur, Saipul; Zainuri, Ahmad (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2023)
In educational institutions, schools must have a facility and infrastructure managementsystem so that activities become effective and efficient. Facilities management andInfrastructure is one of several systems to improve the quality of students. Each schoolhas good facilities and infrastructure for the benefitslearning process. However, simply meeting existing needs can only run well if the management is correct. That way, leadership is needed to regulate existing facilities and infrastructure to achieve the stated goalswill be completed. This article aims to understand the management of educational facilities and school infrastructure.Based on the research results, it can be understood that implementing educational facilities and infrastructure management includes. First, planning facilitiesand infrastructure is always carried out, starting from needs analysis, determining funds and selecting needed goods. Both procurement activities have been running sincedropping government and foundations, procurement by buying. Third, using facilities and infrastructure is always carried out to support learning. Fourth, maintenance of facilities and infrastructure is carried out periodically by involving the school community. The five inventories are always carried out as proof of procurement of goods. Sixth, in the activity of writing off goods, the seven responsibilities are carried out by making an accountability report.